The impact of urban light rail transit on double-story terraced property values in the Greater Kuala Lumpur, Malaysia - Mohd Faris Dziauddin (Tanjung Malim, 2021)
The impact of urban light rail transit on double-story terraced property values in the Greater Kuala Lumpur, Malaysia by Mohd Faris Dziauddin